Hypoglycemia in preterm babies Incidence and risk factors - Aminullah, Asril; Setiati, Dita; Sastroasmoro, Sudigdo (Paediatrica Indonesiana, 2001)
Hypoglycemia is one of the most common problems in neonates, especially in preterm babies. Although in the majority of cases the outcome is good, symptomatic or asymptomatic hypoglycemia may give significant complications that may cause death or developmental delay later in life. We conducted a cross sectional study from September 5, 1999 through May 8, 2000 to identify factors associated with hypoglycemia in preterm babies treated at the Division of Perinatology, Cipto Mangunkusumo Hospital, Jakarta. There were 112 babies included in the study, with the mean gestational age of 33.3 (range 22 to 37, SD 4.2) weeks, and mean birth weight of 1801 (range 850 to 2440, SD 420) grams. Twenty-seven of the 112 infants showed hypoglycemia. Univariate analysis disclosed that birth weight, degree of perinatal asphyxia, small for gestational age (SGA), presence of respiratory distress syndrome, mothers with preeclampsia or eclampsia, and mothers who had intravenous infusion of glucose during labor were significantly associated with hypoglycemia in preterm babies. Gestational age, meconium staining, or infant of diabetic mother were not significantly associated with neonatal hypoglycemia. On logistic regression analysis to control confounders we found that only the degree of perinatal asphyxia and small for gestational age were associated with hypoglycemia in those preterm babies.